Knowledge and Practice Regarding Vitamin-A and its Deficiency among Mothers of under Five Children - M. Patel, Ekta; S. , Adithya; M. Bhakta, Priyasi; M. Prajapati, Bhavika; V. Rathod, Priyanka; M. Patel, Yashvi (International Journal of Psychosocial Rehabilitation, 2020)
Background of the Study: Health care of children under five has been markedly changed in developed countries. Vitamin A deficiency is the second most important factor for global blindness. The under-five children have prime importance, as the mortality and morbidity are higher in this group due to vitamin deficiency disorders. Vitamin A deficiency is one of the most important causes of preventable childhood blindness and is a major contributor to morbidity and mortality from infections. The present study was conducted among mothers of children under five to assess knowledge and practice regarding vitamin A and its deficiency. Material and Methods: A quantitative research approach with a descriptive research design was used. To assess the knowledge regarding vitamin A and its deficiency structured knowledge questionnaire was used. Through checklist practice topic of vitamin A and its deficiency was identified. Results: The collected data was tabulated and analyzed by using descriptive and inferential statistics. The results show that the majority of the samples (90%) had poor knowledge scores, 8.71% had average knowledge scores, and 1.28% had good knowledge scores. The majority of the samples (83%) have demonstrated poor practice, and 17% have demonstrated good practice regarding vitamin A and its deficiency. Conclusions: Significant low levels of knowledge and poor practice regarding vitamin A and its deficiency were found. Knowledge of food-based vitamin A can make sustained improvements in knowledge and dietary practices. Hence, healthcare providers should be trained and encouraged to provide more personalized health education to the mothers of children under five to bring awareness regarding vitamin A and its deficiency.